2012
DOI: 10.1155/2012/319205
|View full text |Cite
|
Sign up to set email alerts
|

CRT-D Therapy in Patients with Decompensated NYHA Class-Four CHF

Abstract: Background. ACC-HRS Guidelines for Cardiac Resynchronization Therapy ICD implantation (CRT-D) do not include patients with advanced nonambulatory NYHA class-four CHF due to an expectation of limited survival. There is little data available from these large multicenter randomized studies to support or refute this claim. Purpose. We evaluated the outcomes of patients with advanced nonambulatory NYHA class-four CHF who received CRT-D devices as an attempt to improve the clinical status and promote hospital discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…A desirable, early hemodynamic effect of CRT immediately after the procedure 12) can facilitate weaning from pharmacological and mechanical support in end-stage HF. 5) As expected, echocardiography revealed rapidly improving LV synchrony and contractility after implantation of CRT, with stabilization of the blood pressure and HR. The patient was successfully weaned from ECMO.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A desirable, early hemodynamic effect of CRT immediately after the procedure 12) can facilitate weaning from pharmacological and mechanical support in end-stage HF. 5) As expected, echocardiography revealed rapidly improving LV synchrony and contractility after implantation of CRT, with stabilization of the blood pressure and HR. The patient was successfully weaned from ECMO.…”
Section: Discussionsupporting
confidence: 73%
“…There have been few selective studies and case reports investigating the usefulness of “rescue” CRT in patients with non-ambulatory New York Heart Association (NYHA) functional class IV HF or cardiogenic shock. 3) 4) 5) 6) 7) Most attempts, however, have been unsuccessful. For example, in a retrospective study by Mantziari et al 3) 24 patients underwent CRT implantation during hospitalization in the cardiac critical care unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, various small studies reported that CRT is an effective therapy in patients with NAHF [7,10–15]. These studies demonstrated favorable outcomes in patients treated with CRT, including the ability to wean patients from intravenous inotropes to oral drugs.…”
Section: Discussionmentioning
confidence: 99%